cos2A+cos2B+Cos2C+cos2(A+B+C)=4cos(B+C)cos(C+A)cos(A+B) prove that
Answers
Answered by
36
= 2cos(A + B)cos (A-B) + 2cos(A +B + 2C)cos(A+B)
= 2cos(A +B){ cos (A-B) + cos (A+ B+ 2c)}
= 2cos (A+ B) {2cos(B +C)cos (A + C)
= 4 cos(A +B)cos(B+C)cos(A+C)
hence,proved
= 2cos(A +B){ cos (A-B) + cos (A+ B+ 2c)}
= 2cos (A+ B) {2cos(B +C)cos (A + C)
= 4 cos(A +B)cos(B+C)cos(A+C)
hence,proved
Answered by
4
Step-by-step explanation:
Hope it helps.
_________Be Delighted_________
Attachments:
![](https://hi-static.z-dn.net/files/dcc/96acc639c04fec88d1b44be3ae5017d2.jpg)
Similar questions